Using Health Belief Model for predicting COVID-19 prevention practices among university student and staff - Hidayati Hidayati; Nia Musniati; Ahmad Hidayat; Mochamad Iqbal Nurmansyah (Intelektual Pustaka Media Utama, 2022)
Large-scale social restriction (PSBB-Pembatasan Sosial Berkala Besar) is a policy aimed at reducing the spread of coronavirus disease 2019 (COVID-19). The purpose of this study was to determine the respondents' compliance behaviors towards the PSBB regulations according to the Health Belief Model. This cross-sectional study was conducted at a private university in Jakarta using quantitative methods. Data collection was carried out on July 2020, where 116 respondents were selected and recruited in the study using convenience non-probability sampling. Online self-administered questionnaire was used to collect data. The independent variables were adopted from Health Belief Model theory. These included; perceived susceptibility, perceived severity, health motivation, perceived benefit, perceived barrier and cues to action. The dependent variable was COVID-19 prevention behavior. Results showed that variables of health motivation (p-value=0.001), perceived benefits (p-value=0.008), and perceived barriers (p-value=0.007), advertising (p-value=0.027), counseling (p-value=0.001), and media access (p-value=0.000) had significant effects on the respondents' compliance to COVID-19 prevention behaviors. Multivariate analysis showed significant association of health motivation and perceived benefits with COVID-19 prevention behavior. An intervention is required to improve the community’s perception and belief towards the benefits and effectiveness of COVID-19 prevention behavior in preventing the COVID-19 pandemic.